Survei Analisis Kebutuhan Pengembangan Lembar Kerja Peserta Didik Berbasis Socio Scientific Issues pada Materi Asam Basa - Aini, Dian Arsy; Solekha, Nuralia Annisatus; Juvitasari, Safira; Nisfah, Ulfa Asrifatun; Tia, Rahma; Siti Aisyah, Ratna Sari; Irhamni, Irhamni; Zidny, Robby (Jambura Journal of Educational Chemistry, 2024)
Socio Scientific Issues (SSI) is an approach that can be used to stimulate students' critical thinking in science learning, especially chemistry learning. This approach can be integrated in the students' worksheet to help students to think critically and achieve learning objectives. The purpose of this study was to determine the responses of chemistry teachers and students of twelve grade secondary school based on the needs analysis of the development of Socio Scientific Issues on Acid-Base topic. The research method used was a survey method using a questionnaire research instrument. This research instrument is filled in through a google form containing several questions or written statements that must be answered by the respondent. The subject of the research were chemistry teachers and XII grade high school students. The results showed that most teachers and students were not familiar with the socio-scientific issue approach in chemistry learning. However, most teachers and students agree to the development of students' worksheet on Acid-Base topic that supports to stimulate critical thinking skills and meaningful chemistry learning.